Moderate stocking density does not influence the behavioural and physiological responses of rainbow trout (Oncorhynchus mykiss) in organic aquaculture. (13th April 2020) - Carbonara, Pierluigi; Alfonso, Sébastien; Gai, Francesco; Gasco, Laura; Palmegiano, Giovanni; Spedicato, Maria Teresa; Zupa, Walter; Lembo, Giuseppe
Abstract: Welfare in farmed fish got particular attention during the last decades from both governmental and public sides. In aquaculture context, welfare concerns are mainly related to handling procedures, water quality and stoking densities. In Europe, authorities had to clarify the threshold limits of stocking densities to maintain fish good welfare, including for organics aquaculture through the EC regulation 710/2009. However, effects of stocking density on fish welfare are complex and sometimes contradictory. Moreover, there is a lack of knowledge about the impact of density on fish welfare in organic aquaculture. Thus, the aim of the study is to asses welfare state of rainbow trout ( Oncorhynchus mykiss ) at two initial stocking densities (low density, LD: 12 kg/m 3 and high density, HD: 17 kg/m 3 ) fed using organic feed by combining the monitoring of growth performances, behaviour (swimming activity) and physiological indicators (i.e. cortisol, glucose, lactate, hematocrit, red blood cellule count and lysozyme). At the end of experiment, the stocking density reached 21 kg/m 3 and 30 kg/m 3 for the LD and HD respectively. Overall, growth performances, swimming activity and level of physiological indicators of stress and welfare were similar between HD and LD over the experiment duration. To conclude, we observed no alteration of fish welfare between the two stocking densities monitored. This study suggests that a final stocking density of 30 kg/m 3 can be considered for organic aquaculture of rainbow trout respecting welfare.